Effect of Heating Time Variation on The Activation of Modified Palm Oil Fly Ash as β-Carotene Adsorbent on Crude Palm Oil - Ginting, Simparmin Boru; Erlangga, Sona; Rustamaji, Heri; Darmansyah; Wijaya, Muhammad Niki; Wardono, Herry (Jurnal Bahan Alam Terbarukan, 2024)
Crude Palm Oil (CPO) contains β-carotene as source of pro-vitamin A. Alternative adsorbent that can be used to adsorb β-carotene is Palm Oil Fly Ash (POFA). This study aims to determine the ability of POFA activated with H3PO4 and Cu/Zn impregnation to adsorb β-carotene from CPO to obtain characteristics data of modified POFA and its ability to adsorb β-carotene. The main materials used were CPO and POFA. The parameters observed were the characterization and performance test of 9% H3PO4-activated POFA produced at various heating times for 90, 150, and 210 minutes with Cu/Zn impregnation. BET analysis showed the POFA with heating time of 90 minutes had the largest surface area of 19.4785 m2/g, XRD showed the presence of CuO, ZnO, quartz, and SiO2 diffraction patterns, FTIR showed that the POFA contained O-H groups, O-H, Si-H, Al-O, asymetric Si-O, and Si-O-Si bending vibrations, and SEM-EDX results showed that POFA has hollow pores and a rough spherical surface. Based on the results of UV-Vis Spectrophotometry analysis, the most optimal result was obtained in the β-carotene adsorption process with POFA-modified 2 variations of activation heating time for 150 minutes, which succeeded in adsorbing 86% of ꞵ-carotene.